Acute Liver Rejection in a Multiple Myeloma Patient Treated with Lenalidomide. (12th December 2020) - Vaxman, Iuliana; Eaton, John; Lee, Hee Eun; Gertz, Morie A.
Abstract : Herein we present a patient that underwent a liver transplant due to primary biliary cholangitis (PBC) and after 9 years developed multiple myeloma. Following the cessation of mycophenolate mofetil and 2 weeks after lenalidomide treatment was started, the patient experienced acute cellular rejection. The patient recovered after treatment with corticosteroids, resumption of mycophenolate mofetil, and cessation of lenalidomide. Lenalidomide-associated allograft rejection has been reported in other organs. However, this is the first case report of liver rejection induced by lenalidomide.